2021
DOI: 10.3389/fcell.2021.718912
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an m6A Regulators-Mediated Prognosis Signature For Survival Prediction and Its Relevance to Immune Infiltration in Melanoma

Abstract: Despite robust evidence for the role of m6A in cancer development and progression, its association with immune infiltration and survival outcomes in melanoma remains obscure. Here, we aimed to develop an m6A-related risk signature to improve prognostic and immunotherapy responder prediction performance in the context of melanoma. We comprehensively analyzed the m6A cluster and immune infiltration phenotypes of public datasets. The TCGA (n = 457) and eleven independent melanoma cohorts (n = 758) were used as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 86 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…IL22RA2 is highly expressed in various tissues, including those in the female reproductive system [ 38 ]. With respect to genes associated with other cancers, NXT2 was among 12 genes used to define prognostic risk groups in melanoma [ 39 ]. A review article described that the aberrant expression of HS3ST3B1 is observed in many cancers, and the authors posited that HS3ST3B1 may act as a tumor-promoting enzyme [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…IL22RA2 is highly expressed in various tissues, including those in the female reproductive system [ 38 ]. With respect to genes associated with other cancers, NXT2 was among 12 genes used to define prognostic risk groups in melanoma [ 39 ]. A review article described that the aberrant expression of HS3ST3B1 is observed in many cancers, and the authors posited that HS3ST3B1 may act as a tumor-promoting enzyme [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…IL22RA2 is highly expressed in various tissues including those in the female reproductive system [37]. With respect to genes associated with other cancers, NXT2 was among 12 genes used to define prognostic risk groups in melanoma [38]. A review article described that aberrant expression of HS3ST3B1 is observed in many cancers and the authors posited that HS3ST3B1 may act as a tumor-promoting enzyme [39].…”
Section: Resultsmentioning
confidence: 99%
“…PAEP, a glycodelin gene, is connected with immune infiltration. It was identified in one study as an independent significant risk factor for Clear Cell Renal Cell Carcinoma (ccRCC) and as one of the survival predictive prognostic markers for melanoma ( Sawyer, 2021 ; Wu et al, 2021 ; Zeng et al, 2022 ). IDE is a multifunctional protease whose main therapeutic areas are neuronal diseases and metabolism.…”
Section: Discussionmentioning
confidence: 99%